United States establishes "level playing field" in broadband - or does it?. - Jones, W.D.
This paper discusses the impact of a recent US FCC decision to eliminate the Brand X ruling that required regional Bell operating companies to make their still-developing broadband networks available to rivals at discounted prices. By doing so, the agency hopes to level the playing field between telephone companies and cable companies. This, in turn, will protect consumers from dramatic price increases and anticompetitive business practices.
Keywords: Baby Bells; Brand X ruling; US Federal Communications Commission; Broadband networks; Broadband services; Cable companies; Data services; Telephone wires